2191. Hepatitis A Outbreak in Southeast Michigan: No Longer a Third World Disease. (26th November 2018) - Altamimi, Sarah; Vahia, Amit; Misikir, Helina; Zervos, Marcus; Reyes, Katherine C
Abstract: Background: Hepatitis A (Hep A) is a self-limiting diarrheal illness occurring in underdeveloped countries. August 2016 marked the onset of an outbreak in Southeast Michigan. Our study characterizes the presentation and clinical course of Hep A patients that presented to our healthcare system. Methods: This study included all Hep A positive cases that presented to Henry Ford Health System from August 2016 to December 2017. Electronic medical records were reviewed for demographics, sexual history, travel history, food exposure, illicit drug use, signs, symptoms and outcomes. Data were also collected on healthcare units of presentation, screening, and care including emergency department, clinic, inpatient hospitalization, or transfer from another facility. Outcomes included hospitalization, consultations with hepatology and transplant, re-admission, and death. Results: A total of 166 cases were reviewed; Figure 1 displays the cases per month. The average age was 51 years and 54% were male. The most common symptoms were abdominal pain (47%) and nausea (42.8). Underlying conditions included illicit drug use (23%), alcohol abuse (22%), and diabetes (18.6%). Three percent of cases traveled outside of the state within 2 weeks prior to diagnosis. Twenty-three percent had history of illicit drug use and 4.2% were food handlers. Table 1 displays the healthcare unit where Hep A serology was ordered. One hundred Twenty-two (73.5%) cases were hospitalized, 44 (26.5%) required ICU admission and seven (4.2%) were readmitted within 30 days. Ninety-two cases (55%) required hepatology evaluation, 25 were evaluated for transplantation and one (0.6%) received a liver transplant. Eighteen (10.8%) patients died, two of which were never hospitalized). Conclusion: High clinical suspicion is crucial during an outbreak. Most of our cases were diagnosed with Hep A during inpatient admission after presenting with abdominal pain and nausea. In an outbreak setting, consider testing for immunity from history of previous exposure or vaccination. High hospital admission, morbidity and mortality were seen. Disclosures: All authors: No reported disclosures.